2017
DOI: 10.1007/s00221-017-5102-5
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum damages learning and memory and suppresses astrocyte–neuron lactate shuttle in rat hippocampus

Abstract: Rare-earth elements (REEs) are applied in various fields by virtue of their superior physical and chemical properties. Surveys have reported that REEs can impair learning and memory in children and induce neurobehavioral abnormalities in animals. However, the mechanism underlying this neurotoxicity is still unclear. Lanthanum (La) is often chosen to study the effects of REEs. Here, we investigated the role of astrocyte-neuron lactate shuttle (ANLS) in spatial learning and memory impairment induced by LaCl in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The same type of analysis conducted on the 12,259 genes using the mammalian phenotype ontology database, revealed enrichment of a series of phenotypes which have been previously linked to the Astrocyte Neuron Lactate Shuttle (ANLS) ( Magistretti and Allaman, 2018 ) and lactate, such as learning ( Tadi et al, 2015 ; Shannon et al, 2016 ; Jin et al, 2017 ) and sleep ( Naylor et al, 2012 ; Petit et al, 2013 ; Haydon, 2017 ), and others for which there are indications of lactate involvement such as hyperactivity and anxiety disorders ( Dillon et al, 1987 ; Russell et al, 2006 ; Johnson et al, 2008 ; Killeen et al, 2013 ).…”
Section: Resultsmentioning
confidence: 92%
“…The same type of analysis conducted on the 12,259 genes using the mammalian phenotype ontology database, revealed enrichment of a series of phenotypes which have been previously linked to the Astrocyte Neuron Lactate Shuttle (ANLS) ( Magistretti and Allaman, 2018 ) and lactate, such as learning ( Tadi et al, 2015 ; Shannon et al, 2016 ; Jin et al, 2017 ) and sleep ( Naylor et al, 2012 ; Petit et al, 2013 ; Haydon, 2017 ), and others for which there are indications of lactate involvement such as hyperactivity and anxiety disorders ( Dillon et al, 1987 ; Russell et al, 2006 ; Johnson et al, 2008 ; Killeen et al, 2013 ).…”
Section: Resultsmentioning
confidence: 92%
“…Future directions in the REE research can be suggested based on our literature search. One obvious research area is the investigation of biological effects of REEs using biochemical, cell biological, and toxicological techniques (Pałasz and Czekaj 2000;Jin et al 2017;Joonas et al 2017;Turra 2018;Romero-Freire et al 2019;Dubé et al 2019;Pałasz et al 2019). Another equally important field is the remediation of REEs in the environment (Su 2017;Yuan et al 2018;Wang 2018;Cheng et al 2018;Wei et al 2019;Jalali et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Some of the toxic effects of REEs were found to be mediated by gene expression changes (Dubé et al 2019) or by directly binding to target proteins (Pałasz and Czekaj 2000). Numerous medical technologies have revealed that various neurophysiological processes including learning and memory were also affected by lanthanides (Pałasz et al 2019;Jin et al 2017). A recent review paper extensively summarized the ecological risks of REEs on plants, animals, and humans' health (Adeel et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Monocarboxylates are essential for sustaining neuronal energy metabolism . Lactate consumption is important for several neurophysiological mechanisms such as respiratory control, sexual impulse and appetite, recovery after cerebral hypoxia, resistance to oxygen and glucose deprivation, neuroprotection and learning and memory processes . MCTs play a central role in lactate uptake in the brain.…”
Section: Discussionmentioning
confidence: 99%